Performance differential between private and state-owned enterprises: An analysis of profitability and leverage - Nguyet Thi Minh Phi; Farhad Taghizadeh-Hesary; Chuc Anh Tu; Naoyuki Yoshino; Chul Ju Kim (Asian Development Bank Institute (ADBI), 2019)
The purpose of this paper is to empirically investigate the relationship between ownership identity and the performance of firms in terms of profitability and solvency. Using cross-sectional data covering over 25,000 firms worldwide and by employing various empirical methods, we find robust support for the inferior performance of government enterprises over privately owned firms. Specifically, state-owned enterprises (SOEs) tend to be less profitable than private-owned enterprises. However, they appear to be more dependent on debt for their financial need and are, thus, better leveraged. Additionally, SOEs are more labor intensive and have higher labor costs. Thus, evidence from this study could be interpreted to mean that privatization could improve the performance of public firms. However, a study over a longer period is needed before these results can be considered conclusive.
Keywords: G32; G341; 330; performance; ownership; solvency; state-owned enterprises; private-owned enterprises